Salivary thromboplastic activity in children with cancer - Tunalı Akbay, Tuğba; Yarat Ayşen; Akyüz, Serap; Pişiriciler, Rabia; Yıldız İnci (My University, 2013)
Thromboplastin is a membrane bound glycoprotein and it is overexpressed in many cancer cells. Chemotherapy induce some alterations in either saliva composition or function leading to oral complications. The aim of this study was to investigate the salivary thromboplastic activity of children with cancer and to compare with healthy children. Saliva samples were taken from 15 children who were diagnosed with lymphoid and solid tumor and from 15 healthy children. In saliva samples thromboplastic activity and total protein levels were determined and SDS polyacrylamide gel electrophoresis was also carried out with these saliva samples. For cytological examination, imprint samples were prepared by applying a drop of saliva on a slide. Salivary thromboplastic activity of children with cancer (CC) was significantly decreased when compared with the healthy children (HC). pH of the saliva in CC was significantly decreased. Salivary flow rate did not significantly change in CC. Saliva total protein level was significantly decreased in CC when compared to HC. In SDS PAGE electrophoresis, some protein bands decreased and some protein bands increased when the two group is compared. In cytologic evaluation of saliva samples, keratinized and dysplastic cells increased in the imprint samples of CC. It should be noted that children receiving chemotherapy encounter major problems in oral and dental health, therefore they need special preventive programs for their oral and dental health
Keywords: Saliva, thromboplastic activity, pH, cancer, salivary cells